2019
DOI: 10.31427/ijstt.2019.2.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis of Intercity Bus Terminal and Inner-City Toll Road Development – The Case of Bandung City

Abstract: This paper explores the impact of Gedebage Terminal development to traffic performance in Bandung City, as well as the development of the inner-city toll road that connects eastern and western part of Bandung City. In addition, the study also analyzes the potential of minibus / public transport route that connects three terminals, namely Gedebage, Cicaheum and Leuwipanjang Terminal, in Bandung City. The study is carried out by using the 4-step modeling principle, by utilizing EMME/4 software. According to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Public transport is any motor vehicle used by the public and charges a specific tariff, either directly or indirectly (Ayuningtyas, Frazila, & Wibowo, 2019). As a link for access between cities, public transportation is significant.…”
Section: Bus and Trainmentioning
confidence: 99%
“…Public transport is any motor vehicle used by the public and charges a specific tariff, either directly or indirectly (Ayuningtyas, Frazila, & Wibowo, 2019). As a link for access between cities, public transportation is significant.…”
Section: Bus and Trainmentioning
confidence: 99%
“…al. [7] analyzed the opportunities to improve public transport in Bandung City by developing three main bus terminals. The study result shows that the addition of an intercity bus terminal will spread the load at the current intercity terminal, which will contribute to improving road performance.…”
Section: Past Studies On Public Transport Planningmentioning
confidence: 99%
“…The study identified the impact of the policies on road network volume capacity ratio, which influences traffic speed, and hence accessibility. A study by [10] also analyzed the impact of terminal development as well as new inner ring road development in Bandung City and its impact in terms of traffic volume, average speed and volume capacity ratio, which are indicators that reflect accessibility. One of the measures that can also be taken to improve accessibility is also through the operation of public transport as a study conducted by [11] which attempts to identify public transport strategies to reduce congestion and improve accessibility in Palembang City, Indonesia.…”
Section: Literature Reviewmentioning
confidence: 99%